Supporting every teacher: Using the Holistic Teacher Assessment (HTA) to measure social-emotional experiences of educators. (November 2022) - Allen, Patricia J.; Bergès, Inès; Joiner, Richard; Noam, Gil G.
Abstract: This study aimed to extend the use of a validated assessment of social-emotional development (SED) from children and adolescents to teachers. We used correlation and regression analyses to examine the factor structure of this Holistic Teacher Assessment (HTA) and the relationships between teacher SED, self-efficacy, and burnout. Results from 284 teachers identified nine interpretable and useful SED dimensions for teachers. SED was a stronger (negative) predictor of burnout than self-efficacy, but together SED and self-efficacy accounted for more variance than either one separately. Supporting every teacher using the strengths-based HTA can inform proactive approaches, tailored to teachers' strengths and needs.